2020
DOI: 10.3390/ijerph17186592
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Aggressive End-of-Life Care among Advanced Cancer Patients in Wuhan, China: A Cross-Sectional Study

Abstract: Life-sustaining treatments (LSTs) and end-of-life (EOL) care’s goal for prolonging one’s life are defined as aggressive EOL care among critically ill patients. They have limited effects and add unnecessary financial burden to advanced cancer patients. A questionnaire survey was conducted to collect information on demographics, disease conditions, preference for LSTs, and goal of EOL care among advanced cancer patients of comprehensive grade-A tertiary hospitals in Wuhan, mainland China. Most patients preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This finding is not surprising as the view of opting for aggressive treatments when patients' health status is reduced is prevailing in China (Gu et al, 2016). Previous research has found that Chinese patients who had little knowledge of EoL care or did not know or inaccurately understand their prognoses when approaching death were more likely to indicate this preference (Liao et al, 2020; Tam et al, 2021). Furthermore, a recent study in Taiwan showed that the discussion of EoL preferences with patients was associated with the option for less aggressive care (Chan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is not surprising as the view of opting for aggressive treatments when patients' health status is reduced is prevailing in China (Gu et al, 2016). Previous research has found that Chinese patients who had little knowledge of EoL care or did not know or inaccurately understand their prognoses when approaching death were more likely to indicate this preference (Liao et al, 2020; Tam et al, 2021). Furthermore, a recent study in Taiwan showed that the discussion of EoL preferences with patients was associated with the option for less aggressive care (Chan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the differences in family culture between the two places. As the traditional Chinese culture emphasizes filial piety and familism, adult children in mainland China regard themselves having responsibilities to take care of their older parents physically and financially at EoL (Liao et al, 2020). By contrast, the HK participants had a lower preference for caring or dying at home.…”
Section: Discussionmentioning
confidence: 99%
“…8-10 While the emerging data are not conclusive, investigators attribute the observed care outcomes to a pattern of family-centered decision-making. 5,11-15…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite the alarming rate of cancer-related mortality, little is known about endof-life (EOL) care of Chinese patients with advanced cancer. [3][4][5][6][7] Limited evidence suggests that Chinese patients with cancer may receive non-beneficial life-sustaining treatments in their final months, including high rates of intensive care unit (ICU) admission, mechanical ventilation, and tube feeding. [8][9][10] While the emerging data are not conclusive, investigators attribute the observed care outcomes to a pattern of family-centered decisionmaking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation